Dental anxiety, pain, and quality of life among exodontia patients: A cross-sectional study - Bamidele A Famurewa; Abimbola A Emmanuel; Omolola T Alade; Michael A Adedigba (Wolters Kluwer Medknow Publications, 2023)
Introduction: There are few studies on dental anxiety (DA) among patients who are planned for routine dental extraction compared with a plethora of published reports on DA and oral health-related quality of life (OHRQoL) in patients undergoing third molar surgery. Aim: This study aims to investigate anxiety level, pain experience and OHRQoL of patients scheduled for routine exodontia at a Nigerian tertiary hospital. Materials and Methods: This was a cross-sectional study conducted at the Oral Surgery clinic of Obafemi Awolowo University Teaching Hospitals Complex, Ile-Ife, Nigeria from April to September 2019. DA, pain, and OHRQoL of participants were assessed using Corah's DA Scale (DAS), Visual Analog Scale (VAS) and 14-item oral health impact profile (OHIP-14) questionnaire, respectively. Just before routine exodontia, the demographic variables of the participants were also recorded. Data were analyzed using R version 4.2.2. Results and Discussion: One hundred fifty-nine participants planned for routine exodontia of one or two permanent tooth/teeth with 41.7 ± 19.8 years mean age. The mean DAS score for the study population was 7.9 ± 3.6 (range: 4-18) with the proportion of dentally anxious patients (DAS score ≥13) being 15.1%. The majority (125; 78.6%) reported preexodontia dental pain VAS score of 4-10. Only 22.6% of the participants had their OHRQoL significantly impaired with OHIP-14 score of 29-56. Conclusion: The prevalence of DA among Nigerian adults scheduled for routine exodontia was 15.1%. At least seven in ten patients had moderate and severe dental pain, while one-fifth presented with significantly impaired OHRQoL.